Experimental characterization and modeling of the temperature and rate-dependent shear behaviour of powder-impregnated glass fiber/PA66 woven semipregs. (18th August 2019) - Baumard, Théo; Menary, Gary; De Almeida, Olivier; Martin, Peter; Schmidt, Fabrice; Bikard, Jérôme
Abstract: This study focuses on the characterization of the in-plane shear response of a novel powder-impregnated, non-consolidated PA66/glass semipreg to evaluate its forming behaviour. The effects of temperature and rate on the behaviour of the semipreg and the preconsolidated material were investigated using bias-extension tests. Results obtained show an increase in shear stress with decreasing temperature and increasing rate, with the semipreg exhibiting a lower sensitivity to the test speed. An increase of the flow distance to impregnate the yarns, due to intra-ply sliding mechanisms specific to the powder-impregnated semipreg, is observed. A model based on a hypoelastic approach with temperature and rate dependence is proposed to represent the material behaviour. Isothermal simulations of the bias-extension test are conducted. Results show a good agreement between the model and experimental data in terms of force and shear angle prediction.